(untitled) (Simbiótica. Revista Eletrônica, 2024)
This article intends to suggest that urban capital appropriates areas previously occupied by industrial plants that left the municipality of São Bernardo do Campo (SP), replacing revenues arising from productive activity with that generated by the exploitation of urban surplus value. To prove this hypothesis: a) we correlated data on real estate units launched in the city with the reduction in the share of industrial activity and the increase in services activity in the municipality’s GDP; b) we analyzed the weight of donations from the construction sector in municipal elections (until 2015); c) we highlighted the increase in IPTU and ISS revenue and its translation into investment in the city’s urban development policy, through the analysis of urban expenditure budget data.